Object of learning in the teaching of simple harmonic motion: a case study using active methodology (ISLE type) (Research, Society and Development, 2021)
In classroom, the Simple Harmonic Movement (SHM) is a content generally seen only in the form of expository classes and, for this reason, considered difficult to understand. In order to solve this problem, the following research question was asked: does the Learning Object (LO) contribute to the understanding of SHM, based on the ISLE Methodology approach? For that, simulations of SMH graphics were created with the aid of digital tools. This research was carried out at IFCE Campus Fortaleza and its main objective was to analyze the use of a LO in the discipline of Physics, aiming to assist the student in the simulation of graphs of the Simple Harmonic Movement (SHM), supported by the Active Methodology of the ISLE type, which proposes a Science Investigative Learning Environment. The students performed a pre-test in which they were to analyze and interpret the data of an SHM from its graph. Then, using the LO, the students explored the variables present in a periodic movement, being able to interact with it and visualizing the changes in the movement and in the graphs related to it. Finally, the students performed a post-test that consisted of, again, interpreting an SHM phenomenon based on its graph and producing new graphs representing other of its variables. The results point to an improvement in the understanding of the learners regarding the studied subject, indicating that the use of digital tools and active methodologies can contribute to a meaningful learning of Physics concepts, more specifically, of the SHM.